Implementasi Nilai-Nilai Filsafat Pendidikan dalam Pembelajaran Sekolah Dasar: Penelitian - Thresia Yohana Sembiring; Weni Sarbaini (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the implementation of educational philosophy values ​​in the learning process in Elementary Schools. The research approach used is descriptive qualitative, with data collection techniques in the form of observation, interviews, and literature studies. The results of the study indicate that values ​​such as humanism, existentialism, constructivism, and progressivism have begun to be applied by teachers in learning activities, especially in the context of the Independent Curriculum. Teachers show concern for the individual needs of students, provide limited freedom, and encourage active learning based on experience. However, the application of these values ​​is not fully based on systematic philosophical awareness. Therefore, it is necessary to strengthen the understanding of educational philosophy in teacher education in order to be able to integrate these values ​​completely and consistently in the learning process.